Use analysis of internal growth rate and sustainable growth rate and its relation to performance - Hussain Hadi Al-Nasser, Aqdas; Mahdi Atiyah Al-Jubouri, A.D. (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to study the relationship between the rate of sustainable growth and internal growth rate and the improvement of the performance of the company and the degree of relationship between these variables. For this purpose, a sample of the listed companies was used in the Iraqi Stock Exchange for 22 companies for the period 2010-2017 through use of the financial statements of the sample companies. The research focused on the data related to the internal rate of return (EGR), sustainable rate of return (SGR) General revenue using analytical statistical methods and methods such as the Mann-Whitney U and Spearman correlation tests and using the SPSS statistical program. V22. Linear regression analysis was used to examine the correlation between the deviation of the actual growth rate from the sustainable growth rate, return on assets (ROA), price to book value (P / B), community ratios and rapid rate. The study showed that there is a correlation between ROA and IGR and SGR and is not significant with the general rate of return. The results also showed a relationship and impact between most operational efficiency indicators, IGR and SGR.